AZOLLA PINNATA DANBLUE-GREEN ALGAESEBAGAI BIOFERTILIZER PADASYSTEM OF RICE INTENSIFICATION (SRI). - Hati, Diah Puspita (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2012)
This study aims to determine the effect of Azollapinnata and Blue - green Algae As Biofertilizer on System of Rice Intensification ( SRI ). This study was conducted from March 2010 to June 2010 in the greenhouse of the Faculty of Agriculture, University of Padjadjaran, Jatinangor, Sumedang. The research location is at an altitude of ± 700 mdpl . This experiment used a randomized block design (RAK) factorial consisting of two treatments Azollapinnata (4 stage treatment ), namely: a0 = without Azolla ; pot -1 Azolla; a2 = 50 g pot -1 Azolla; a3 = 75 g pot -1 Azolla dan Blue-green Algae ( 3 stage treatment ) , namely : b0 = without BGA ; b1 = 0.05 lt pot-1 BGA; b2 = 0.1 lt pot-1BGA with three replications. The results showed Azollapinnataproviding various treatments and BGA does not significantly affect the growth of rice plants SRI.Perlakuana3b1 provide the highest influence on the number of tillers and a0b2 treatment gave the highest effect on plant height and plant height difference . However a3b1 treatment gives the best effect because it is more consistent both in the number of tillers and plant height.